Detection of Cardiac Functions of Fetus with Diabetic Metabolic Disease through PEG-PCLNano Micelle and Ultrasound Technique: Detection of Cardiac Functions of Fetus with Diabetic Metabolic Disease - Ran, Hongmei; Zhang, Yunlong; Yu, Dingding; Zhou, Guoli (Cellular and Molecular Biology, 2022)
The study was to probe into the application of ultrasound technique in gestational diabetes mellitus (GDM) and research the progress of PEG-PCL nano micelle and ultrasound technique. Method: 210 patients with a singleton pregnancy fetus, who received the fetal echocardiography in Yuhang District First People's Hospital from March 2019 to March 2020, were selected as the subjects, including 101 fetuses who were confirmed as gestational diabetes mellitus(GDM), and 109 normal fetuses (control group). The ultrasound cardiogram technique was employed to detect the thickness of the fetus ventricle septum, mitral/tricuspid annular displacement, left/right TEI indexes, and so on. The mean value of three cardiac cycles was taken as the test results. Finally, SPSS17.0 software was applied to the analysis of data. The nano micelle was made from the amphiphilic block copolymers (PEG-PCL) using the dialysis method/solvent evaporation method. The nanoscale ultrasound contrast agent was prepared from Decafluoropentane which was imaging gas. The characterizations were studied using the optical microscope, and transmission electron microscopy (TEM). The temperature sensitivity and ultrasound sensitivity of the nano-ultrasound contrast agent were analyzed with the particle size as the evaluation index. The in-vitro ultrasound contrast experiment was conducted to study the contrast-enhanced effect. Results: The fetal Tei index of the case group was higher than that of the control group, of which P<0.05 had statistical significance. However, the thickness of the fetus ventricle septum, Em, Am, and Em/Am of mitral/tricuspid annular were not significantly different from those of the control group (P>0.05). The nano ultrasonic contrast agent prepared through the ultrasonic injection method had a uniform particle size and a hollow shell-core structure under an electron projection microscope. The particle size of the nano-ultrasound contrast agent varied with temperature, and its microbubbles were generated under ultrasonic conditions. As compared with the blank degassed water group, a real linear echo appeared inside the contrast agent group, with small and even echo spots. The back echo remained with no obvious attenuation and lasted for a longer period. However, the blank degassed group had no distinct echo intensity and spot. Conclusion: PEG-PCL nano-ultrasound contrast agent achieved an excellent imaging effect; there was no obvious change to heart function and structure of the fetus, when gestational diabetes pregnant had blood sugar perfectly controlled, however, the fetus’s heart function may change in the last trimester.